Morphometric-stereological and functional epididymal alterations and a decrease in fertility in rats treated with finasteride and after a 30-day post-treatment recovery period - Garcia, Patrick Vianna; Barbieri, Mainara Ferreira; Perobelli, Juliana Elaine [UNESP]; Consonni, Silvio Roberto; Paccola Mesquita, Suzana de Fatima; Kempinas, Wilma de Grava [UNESP]; Violin Pereira, Luis Antonio (Elsevier B.V., 2012)
Objective: To evaluate morphometric-stereological changes in the epididymal caput, sperm quality, and fertility parameters in rats treated with finasteride and after a 30-day post-treatment recovery period.Design: Experimental study in a research laboratory.Setting: Reproductive biology research laboratory.Animal(s): Male and female Sprague Dawley rats.Intervention(s): Treatment with finasteride (5 mg/kg/day) for 56 days followed by 30 days without treatment.Main Outcome Measure(s): Serum hormone analyses, morphometric-stereological and ultrastructural evaluation of the epididymal caput, sperm transit time, natural mating, in utero insemination, sperm membrane integrity, and fertility parameters.Result(s): Serum dihydrotestosterone levels in the finasteride group decreased by similar to 40% compared with that of control rats. Ultrastructural analysis revealed significant reductions in several morphometric-stereological parameters of the epididymal caput. All parameters recovered significantly in the post-treatment period. There was no alteration in daily sperm production in the finasteride group. However, significant reductions in sperm transit time, motility, sperm membrane integrity, and fertility parameters were observed in rats treated with finasteride.Conclusion(s): Treatment with finasteride caused morphometric-stereological and functional changes in the epididymis and in sperm function that led to a reduction in fertility parameters. A 30-day post-treatment recovery period was insufficient to restore normal sperm motility, sperm transit time, and some fertility parameters. (Fertil Steril (R) 2012;97:1444-51. (C) 2012 by American Society for Reproductive Medicine.)
Keywords: Finasteride; epididymis; sperm and fertility